Influence of training load on upper respiratory tract infection incidence and antigen‐stimulated cytokine production. Issue 4 (12th December 2011) - Gleeson, M.; Bishop, N.; Oliveira, M.; Tauler, P.
Abstract : This study examined the effect of training load on upper respiratory tract infection (URTI) incidence in men and women engaged in endurance‐based physical activity during winter and sought to establish if there are training‐associated differences in immune function related to patterns of illness. Seventy‐five individuals provided resting blood and saliva samples for determination of markers of systemic immunity. Weekly training and illness logs were kept for the following 4 months. Comparisons were made between subjects ( n  = 25) who reported that they exercised 3–6 h/week (LOW), 7–10 h/week (MED) or ≥ 11 h/week (HIGH). The HIGH and MED groups had more URTI episodes than the LOW group (2.4 ± 2.8 and 2.6 ± 2.2 vs 1.0 ± 1.6, respectively: P  < 0.05). The HIGH group had approximately threefold higher interleukin (IL)‐2, IL‐4 and IL‐10 production (all P  < 0.05) by antigen‐stimulated whole blood culture than the LOW group and the MED group had twofold higher IL‐10 production than the LOW group ( P  < 0.05). Other immune variables were not influenced by training load. It is concluded that high levels of physical activity are associated with increased risk of URTI and this may be related to an elevated anti‐inflammatory cytokine response to antigen challenge.